Eccentric Connectivity and Zagreb Coindices of the Generalized Hierarchical Product of Graphs. (27th November 2014) - Tavakoli, M.; Rahbarnia, F.; Ashrafi, A. R.
Abstract : Formulas for calculations of the eccentric connectivity index and Zagreb coindices of graphs under generalized hierarchical product are presented. As an application, explicit formulas for eccentric connectivity index and Zagreb coindices of some chemical graphs are obtained.